Konsumsi dan kecernaan nutrien, serta kinerja pertumbuhan kambing Kacang muda dilihat dari perbedaan jenis kelamin dan perlakuan kastrasi - Paulus Klau Tahuk; Gerson Frans Bira (Livestock and Animal Research, 2022)
Objective: This study aims to determine the intake, digestibility of nutriens and growth performance Kacang goats that were given complete feed in terms of sex differences, and castration treatment.Methods: The research took place in the experimental enclosure of the faculty of Agriculture, Timor University from Marh to October 2021. The livestock used were 15 young Kacang goats, which were divided into 3 treatment groups. The three livestock treatment groups were T1 (a group of castrated male Kacang goats), T2 (a group of young male Kacang goats without castration), and T3 (a group of young female Kacang goats). The three groups of goats were given a complete ration consisting of 30% corn straw + 20% gamal + 30% milled corn + 15% pollard bran + 5% rice bran. The variables observed included nutrien consumption and digestibility as well as livestock growth performance.Results: The results showed that the treatment had no significant effect (P>0,05) on the intake of DM, OM and CP; Likewise, the digestibility of DM and OM was relativeely the same, except for the digestibility of CP which showed a significant effect (P<0.05). Livestock growth performance was not much different between young castrated male Kacang goats, non-castrated goats and female goats.Conclusions: Castrated young Kacang goats, without castration and female Kacang goats given complete feed showed similar performance in terms of nutrien intake and digestibility, as well as daily body weight gain.